2022
DOI: 10.1021/acs.organomet.2c00424
|View full text |Cite
|
Sign up to set email alerts
|

Organozinc Fluoride and Trifluoromethyl Compounds Supported by the Bis(2-pyridylthio)methyl Ligand

Abstract: The bis(2-pyridylthio)methyl ligand, [Bptm], has been employed in the synthesis of {[Bptm]Zn(μ-F)} 2 , a rare example of an organozinc fluoride compound. The dimeric nature of {[Bptm]Zn(μ-F)} 2 , which possesses an uncommon [Zn(μ-F)] 2 motif, contrasts with the monomeric structures reported for the other halide derivatives, [Bptm]ZnX (X = Cl, Br, I); this difference is supported by density functional theory calculations which indicate that the fluoride derivative favors a dimeric form with bridging fluoride li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 207 publications
0
3
0
Order By: Relevance
“…In addition, when the reaction of I−(CF 2 ) n −I (n=3, 4, 6) 8 with ZnEt 2 was carried out in hexanes, the reaction system gave dizinc reagents 2 a – c in 82–86 % yields [24] . Shlian and Parkin showed that trifluoromethylation of [Zn(bptm)(μ‐F)] 2 9 with Me 3 SiCF 3 in C 6 D 6 at 90 °C for 24 h afforded [Zn(CF 3 )(bptm)] 3 , whose Zn−CF 3 bond length was 2.016(3) Å, shorter to those in [Zn(CF 3 ) 2 (py) 2 ] [2.056(3) Å and 2.069(4) Å] and longer than the corresponding Zn−CH 3 bond length (1.984(3) Å) in [Zn(CH 3 )(bptm)], respectively [25] . Moreover, the reaction of ZnEt 2 10 , fluoroalkyl iodides (R F I) 11 as well as 1,3‐dimethyl‐3,4,5,6‐tetrahydro‐2(1 H )‐pyrimidinone (DMPU) in hexane at −20~0 °C or −15~23 °C provided the white powders [Zn(R F ) 2 (DMPU) 2 ] 4 a – f in 67–95 % yields ( 4 a : 90 %, 4 b : 86 %, 4 c : 95 %, 4 d : 88 %, 4e: 67 %, 4 f : 87 %) [26,27] .…”
Section: Synthesis Of Well‐defined Fluoroalkyl Zinc Complexesmentioning
confidence: 87%
See 2 more Smart Citations
“…In addition, when the reaction of I−(CF 2 ) n −I (n=3, 4, 6) 8 with ZnEt 2 was carried out in hexanes, the reaction system gave dizinc reagents 2 a – c in 82–86 % yields [24] . Shlian and Parkin showed that trifluoromethylation of [Zn(bptm)(μ‐F)] 2 9 with Me 3 SiCF 3 in C 6 D 6 at 90 °C for 24 h afforded [Zn(CF 3 )(bptm)] 3 , whose Zn−CF 3 bond length was 2.016(3) Å, shorter to those in [Zn(CF 3 ) 2 (py) 2 ] [2.056(3) Å and 2.069(4) Å] and longer than the corresponding Zn−CH 3 bond length (1.984(3) Å) in [Zn(CH 3 )(bptm)], respectively [25] . Moreover, the reaction of ZnEt 2 10 , fluoroalkyl iodides (R F I) 11 as well as 1,3‐dimethyl‐3,4,5,6‐tetrahydro‐2(1 H )‐pyrimidinone (DMPU) in hexane at −20~0 °C or −15~23 °C provided the white powders [Zn(R F ) 2 (DMPU) 2 ] 4 a – f in 67–95 % yields ( 4 a : 90 %, 4 b : 86 %, 4 c : 95 %, 4 d : 88 %, 4e: 67 %, 4 f : 87 %) [26,27] .…”
Section: Synthesis Of Well‐defined Fluoroalkyl Zinc Complexesmentioning
confidence: 87%
“…From 2014 to 2022, an efficient protocol for the preparation of perfluoroalkyl zinc complexes 1-6 was reported by the groups of Vicic, Parkin, Monfette, Mikami and Li (Scheme 2). [24][25][26][27][28] Vicic and co-workers reported that the reaction between Br(CF 2 ) 4 Br 7 and metallic zinc in diglyme at 80 °C for 20 min delivered 76 % yield of [Zn 2 (CF 2 ) 4 (digylme) 2 (Br) 2 ] 1, which had excellent thermal stability in acetonitrile. [24] It is interesting that complex 1 precipitates from a solution of diglyme and can be obtained by simple filtration without further purification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation